Szűz Mária alakja a vallásos ponyvairodalomban - Lengyel Ágnes (Szegedi vallási néprajzi könyvtár, 2001)
The paper investigates, systematises the material related to Virgin Mary in religious popular literature becoming widespread in the second half of the 19й1 century. The research is mainly based on recent material, from the counties of Nógrád and historical Hont. According to thematic elements the analysed material is categorised into the following groups: life of Virgin Mary, calendar festivals, shorter periods (a month, a week, a day), shrines devoted to Blessed Mary, confratenities, extreme life situations, general cult. Concrete examples in each category are to illustrate. This categorisation of the booklets also presents the occasions of their usage. The texts were used mainly during common prayersled by foresingers and pilgrimage leaders, again in crisis situations or in private devotion. The image of Virgin Mary expressed in small religious booklets is rather diverse and complex from religious historical, poetical and folkloristic point of view. Even within one bookletthere are several different genres,such aslaments, prayers, hymns, etc., which may be either the texts of official service-books or lay, even officially prohibited hymns, also individual works by a concrete author. In this complexity there are texts going back to the apocryphal gospels containing medieval elements, while some are descriptions of recent phenomena. The paper deals with the role of popular texts in folklife, also their connection to folkbelief. Besides it discusses the significance and names of Blessed Mary reflected int he texts.